Trust management and evaluation for edge intelligence in the Internet of Things. (September 2020) - Qureshi, Kashif Naseer; Iftikhar, Abeer; Bhatti, Shahid Nazeer; Piccialli, Francesco; Giampaolo, Fabio; Jeon, Gwanggil
Abstract: Information and Communication Technologies (ICTs) have revolutionised the traditional communication processes, converting the cities into Smart Cities. Internet of Things (IoT) is one of the leading frameworks in Smart Cities realm; it is based on heterogeneous infrastructure, digital systems, smart technologies, and intelligent services. Due to the complex networks supporting the IoT world, smart devices and services are quickly degrading due to various factors. Security is one of the considered factors, and it also represents a difficult challenge. Malicious nodes disrupt the data traffic and integrity of IoT-based networks. This paper presents a novel Cumulative Trust Evaluation based Efficient Technique (CTBET) by singling out numerous viewpoints on governing and implementing the security in edge-based IoT networks. The proposed CTBET is based on the cumulative trust concept, which calculates the direct and indirect trust among nodes considering the packet drop rate and the packet data rate among different transmission nodes. Furthermore, it enforces suitable approaches to implement the trust mechanism based technique to enhance security and privacy. The proposed scheme handles the On-Off, Denial of Service (DoS) and Bad-Mouth attacks and is also able to isolate the malicious nodes in edge-based IoT networks. The provided simulation results show encouraging performance in terms of network life span, level of trustworthiness of nodes, lesser end-to-end delay and high data delivery ratio, during data transmission in the presence of the malicious and selfish nodes in the network.